Economic effects of the Khon Kaen - Yang Talad feeder road in Northeast Thailand - Nit Jittasatra; Jones, John Hugh; Michelin, F. S.; Chai Muktabhant (Bangkok : SEATO Graduate School of Engineering, 1967)
The objective of this study has been to investigate the role of the Khon Kaen-Yang Talad feeder road in the economic development of the region in which it is located. The study area traversed by this road comprises Tambol (Sub-district) Pralab in Amphur (District) Muang Khon Kaen, Amphur Chieng Yuen in Changwad (Province) Mahasarakam, and Amphur Yang Talad in Changwad Kalasin. General concepts pertaining to economic benefits, mainly indirect benefits, which may be induced by the construction of development roads are presented. Certain of these economic effects were selected for detailed analysis. Indirect benefits were assessed from agricultural economic development, forestry product development, educational development, health facility development, and the development of business and commercial activity in the study region. Each aspect that was studied utilized a combination of cross sectional and time-series analysis. Time-series changes in agricultural production, forest production, and business activity were investigated by comparing the data with that of a reference area. To ensure that the reference area had generally similar environmental conditions, the datum was the larger geographical (and political) division of which the study area was a component. The datum regions selected were Changwad Mahasarakam excluding Amphur Chieng Yuen, and Changwad Kalasin excluding Amphur Yang Talad. Prior to the construction of the feeder road, transportation facilities, population growth trends, amount of rainfall, agricultural conditions, distribution of agricultural production by type, public policy, and other environmental conditions in the study area and the datum regions were similar. Conclusions have been drawn pertaining to the economic effects of feeder roads in Northeast Thailand
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in the SEATO Graduate School of Engineering, Bangkok, Thailand
Thesis (M.Eng.) - SEATO Graduate School of Engineering, 1967
Keywords: Roads -- Economic aspects -- Thailand, Northeastern